Proliferation activity in the polyps of Cassiopea xamachana: where the planuloid buds grow - Khabibulina, Valeriia; Starunov, Viktor (Biological Communications, 2021)
Polyps of the Cassiopeidae family possess a unique type of asexual reproduction by producing free-swimming buds — planuloids. The process of planuloid development and transformation to polyp has been described earlier, however, the source of tissue formation is still poorly studied. Using the method of EdU incorporation we have analyzed DNA synthesis activity during planuloid formation and growth in Cassiopea xamachana. We revealed the active proliferation zone at the early stage of bud formation. This zone continued to function during planuloid growth, providing the formation of polyp structures, and preserved in polyp calyx after metamorphosis. Its proliferation activity varied at different growth stages, whereas the localization remained relatively the same.